Purchase task sensitivity to drug and nondrug reinforcers in opioid‐agonist treatment patients. Issue 3 (15th February 2021) - Schwartz, Lindsay P.; Silberberg, Alan; Hursh, Steven R.
Abstract : The behavioral economics of substance abuse has been increasingly recognized as a method of determining the value of abused substances for individuals who use those substances. It has been hypothesized that such analyses could serve as a clinical tool and that demand functions can be targeted predictors for the level of intervention necessary. This study evaluated the sensitivity of a demand task in 2 patient groups in a medication assisted treatment program (methadone maintenance), those who had used opioids in the last 2 months and those who had not used opioids in at least 18 months. Demand for 7 drugs and a control was assessed using hypothetical purchase tasks. Participants maintaining long‐term abstinence had significantly higher α (sensitivity to price) and lower Q 0 (intensity of demand) for heroin than participants who had recently used opioids. Further research is necessary to illustrate if treatment is responsible for this reduction in demand. If so, demand analyses may provide clinical utility as an aid for treatment planning or as a target for treatment.